Studies On Electrical Conductance Of Novel Random Copolymers And Photocrosslinking Efficacy Of Their Blend - D. Roopsingh, C.Rajam (International Journal of Scientific Research and Management (IJSRM), 2015)
A series of novel random copolymers with oxygen bridges were prepared from4,4’-oxybisbenzoicacid and 1,6- hexandiol/arylidenediol with varying diols namely, 1,8-dihydroxyanthraquinone, 4,4’-dihydroxydiphenyl and 4,4’- diamino diphenyl -methane using diphenylchlorophosphate as the condensation agent. Their structural features were investigated by viscosity measurements, FTIR, 1HNMR and 13CNMR spectral data and thermal behavior was established by Differential Scanning Calorimetry (DSC) and Hot Stage Optical Polarised Microscopy (HOPM). The synthesized polymers/PVC blend nanofibers drawn by electrospinning process were tested for photocrosslinking efficacy using UV irradiation technique. The changes in morphology of the nanofibers by UV irradiation were studied by Scanning Electron Microscopy (SEM). The frequency dependent dielectric and conductivity behaviour of the synthesized polymers were studied at different temperatures using LCR meter. The synthesized polymers with such unique properties are expected to be of use in electrochemical devices and sensors